The Second wave of Look East Policy (LEP 2.0): enhancing the bilateral relations between Malaysia – Japan - Hanim Ismail; Ahmad Faiz Yaakob (Penerbit Universiti Kebangsaan Malaysia, 2024)
Japan was among the first countries to establish diplomatic relations with Malaya (then Malaysia). On 9 September 1957, nine days after Malaya achieved independence, Japan opened its embassy in Kuala Lumpur. The introduction of the Look East Policy (LEP) in 1982 strengthened the existing Malaysia-Japan bilateral relations. The main objective of this study is to examine the nature of the bilateral relationship between Malaysia and Japan during the implementation of the Look East Policy (LEP) and to identify the mutual benefits obtained by both countries in the implementation of LEP 2.0. This study adopted a qualitative analysis method by conducting intensive interviews and focus group discussion involving 13 informants who were directly involved with the implementation of LEP. The study found that, among other things, while LEP made the good practice of the Japanese people as the main driving factor, it also included the Japanese work culture, discipline, ethics, integrity, accountability, management and strategic partners. Three decades after the implementation of LEP in Malaysia, LEP took up a notch with the introduction of the Second Wave of LEP in 2012. Otherwise known as LEP 2.0, it prioritised new areas in line with technological developments in the millennial era. In line with that, LEP 2.0 also focused on the context of mutual benefit (common interest) for both countries especially in Halal hub industry and tourism.